TREATMENT FOR THE CHRONIC HEPATITIS B AMONG CHILDREN - T.V. Strokova; O.S. Gundobina; A.B. Galich; T.B. Sentsova; E.L. Tumanova; V.M. Senyakovich; A.S. Potapov; B.S. Kaganov (Union of pediatricians of Russia, 2007)
The article demonstrates the results of the clinical efficiency and tolerance of different antiviral therapy schemes (interferon, lamivudin and their combination) among children with chronic hepatitis b. the comparative research involved 85 children, who underwent the examination of the biochemical blood analysis, hepatitis b markers (Elisa, PCR), histological study of the liver tissues.Key words: children, chronic hepatitis b, interferon, lamivudin.